2023
DOI: 10.1111/jvh.13818
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment with direct‐acting antivirals on inflammatory markers and autoantibodies in HIV/HCV co‐infected individuals

Abstract: HCV infection could have extrahepatic manifestations due to an aberrant immune response. HCV/HIV co‐infection increases such persistent immune activation. Aim of the present study is to describe the evolution of inflammatory markers used in clinical practice, mixed cryoglobulinemia (MC) and autoantibody reactivity in co‐infected individuals who achieved sustained virological response (SVR) after DAA treatment. This prospective, observational study included all HIV/HCV co‐infected subjects who started any DAA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Other studies have demonstrated the impact of HCV cure on reduction in other markers predictive of non–AIDS-related complications after DAA therapy in people with HCV/HIV coinfection [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated the impact of HCV cure on reduction in other markers predictive of non–AIDS-related complications after DAA therapy in people with HCV/HIV coinfection [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…
Dear Editors,We read with great interest the recent paper by Rossotti et al which showed that direct-acting antiviral (DAA) treatment may improve inflammatory markers levels, without significant changes in CD4/ CD8 ratio, over a 12-week follow-up in HIV/hepatitis C virus (HCV) co-infected individuals. 1 The clinical utility of CD4/CD8 ratio monitoring in people living with HIV (PLWH) is increasingly recognized, especially among individuals with controlled infection. 2 Substance (including tobacco, alcohol and cannabis) use, frequently reported by PLWH, is rarely cited as a determinant of CD4/CD8 variations, 2 while it may impact CD4 and CD8 cell counts.
…”
mentioning
confidence: 99%